Facile synthesis of NHC-stabilized Ni nanoparticles and their catalytic application in the Z-selective hydrogenation of alkynes. Issue 56 (8th May 2017) - de los Bernardos, Miriam Díaz; Pérez-Rodríguez, Sara; Gual, Aitor; Claver, Carmen; Godard, Cyril
Abstract : Well defined Ni nanoparticles stabilized with N-heterocyclic carbenes have been synthesized through decarboxylation of a zwitterionic CO2 adduct and they selectively hydrogenate internal alkynes into ( Z )-alkenes under mild reaction conditions. Abstract : Well defined Ni nanoparticles (NiNPs) stabilized with N-heterocyclic carbenes (NHCs) have been synthesized through a new methodology involving the decarboxylation of a zwitterionic CO2 adduct. Their catalytic performance was tested in the partial hydrogenation of alkynes into ( Z )-alkenes under very mild reaction conditions (50 °C and 5 bar H2 pressure), providing excellent activities and selectivities.